(untitled) (Hoboken, N.J., 2014)
This hands-on resource arms you with an arsenal of advanced investing techniques for everything from stocks and futures to options and exchange-traded funds. You'll find out how to trade on the FOREX market, evaluate annuities, choose the right commodities, and buy into hedge funds. Plus, you'll get up to speed on using business fundamentals and technical analysis to help you make smarter decisions and maximize your returns. You'll also find ways to be as aggressive as your personality and bank account allow, without taking foolish or excessive risks.
Keywords: Investments,Speculation,Đầu tư,Đầu cơ